ANALYSIS OF THE EFFECT OF DIVERSIFICATION AND INTELLECTUAL CAPITAL ON CORPORATE FINANCIAL PERFORMANCE WITH GOOD CORPORATE GOVERNANCE AS A MODERATOR - Mohamad Ghofur; Nofryanti; Iin Rosini (ZILLZELL MEDIA PRIMA, 2024)
This study aims to explore the relationship between diversification strategy, intellectual capital, and firm performance, with good corporate governance as a moderating variable. This study was conducted on companies listed in the Kompas 100 index during the period 2018 to 2022. The purposive sampling method was used to collect 140 samples, and data analysis was conducted using the Random Effect method using EViews 12 software. The results showed that diversification strategy has no significant influence on the performance of companies in the Kompas 100 index. In contrast, intellectual capital shows a significant positive influence on firm performance. Good corporate governance does not moderate the relationship between diversification strategy and firm performance, and is unable to moderate the effect of intellectual capital on firm performance. These findings provide important insights for corporate managers and researchers interested in understanding the factors that influence firm performance in the context of the dynamics of the global business environment.